Silencing RPL11 attenuates acute kidney injury by suppressing tubular apoptosis and macrophage-driven inflammation - Dong, Qian; Xu, Huan; Xu, Pengjie; Liu, Jiang; Shen, Zhouji; Li, Yabin (Frontiers in Immunology, 2025)
BackgroundAcute kidney injury (AKI) remains a life-threatening syndrome with elusive molecular drivers. Although ribosomal proteins such as RPL11 are increasingly recognized for their extra-ribosomal functions, their roles in AKI pathogenesis remain unexplored.MethodsThe comprehensive multi-omics analysis of mouse AKI kidneys combined scRNA-seq and RNA-seq to identify core regulatory factors. Based on cisplatin induced AKI, a HK-2 cell model was established by siRNA transfection silencing RPL11, while in vivo kidney targeted silencing was achieved using LyP-1 modified nanoparticles encapsulating si-RPL11. Technologies such as Western blotting, qPCR, and IVS fluorescence imaging ensure the successful construction of cell and animal models. Functional testing includes CCK-8, EdU assay, flow cytometry, TUNEL assay, qPCR, ELISA, and histopathological techniques to evaluate cell proliferation, apoptosis, and inflammatory cytokine levels.ResultsRPL11 was identified as the core gene with AKI-specific upregulation in proximal tubules. RPL11 expression correlated with AKI severity and showed positive associations with Scr/KIM-1. The specific silencing of RPL11 in HK-2 cells was successfully induced and the LYS-1 peptide-modified cationic liposome nanoparticles were stable in quality and could target the renal tissue of AKI mice to silence RPL11. The experimental results have jointly confirmed that RPL11 suppressed proliferation, accelerated apoptosis, amplified inflammation and aggravated tubular necrosis and CD68 macrophage infiltration in vitro and in vivo.ConclusionRPL11 drives AKI progression by orchestrating tubular dysfunction, apoptosis, and immune dysregulation. Our renal-targeted nano-intervention validates RPL11 as a therapeutically actionable target, providing a novel strategy for biomarker-guided AKI management.